The global position of the EU in complex technologies - Valentina Di Girolamo; Alessio Mitra; Julien Ravet; Océane Peiffer-Smadja; Pierre-Alexandre Balland (Publications Office of the European Union, 2023)
This paper studies the relationship between knowledge complexity and countries' technological dependency, with a focus on the EU's position vis-à-vis other major economies. Using patent data, we calculate the knowledge complexity index at technological level for a set of countries over the period 1990-2020 to assess the EU's technological capabilities. Our findings show that the EU's overall position has progressively worsened vis-à-vis the US, China, Japan, and South Korea over the last three decades, that the EU's technological base is more diversified than that of other major economies, but is disproportionally more specialised in less complex technologies than its counterparts. Finally, the EU is particularly dependent on just a few countries in most complex technologies.
Keywords: O11; O33; 330; Complex technologies; Technological dependencies; Strategic autonomy; Relatedness